Cellular Chitchatting: Exploring the Role of Exosomes as Cardiovascular Risk Factors - Germena, Giulia; Zelarayán, Laura Cecilia; Hinkel, Rabea (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are small bi-lipid membranous vesicles (30-150nm) containing different biological material such as proteins, lipids and nucleic acid. These small vesicles, inducing a cell to cell signaling pathway, are able to mediate multidirectional crosstalk to maintain homeostasis or modulate disease processes. With their various contents, exosomes sort and transfer specific information from their origin to a recipient cell, from a tissue or organ in the close proximity or at distance, generating an intra-inter tissue or organ communication. In the last decade exosomes have been identified in multiple organs and fluids under different pathological conditions. In particular, while the content and the abundance of exosome is now a diagnostic marker for cardiovascular diseases, their role in context-specific physiological and pathophysiological conditions in the cardiovascular system remains largely unknown. We summarize here the current knowledge on the role of exosomes as mediators of cardiovascular diseases in several pathophysiological conditions such as atherosclerosis and diabetes. In addition, we describe evidence of intercellular connection among multiple cell type (cardiac, vasculature, immune cells) as well as the challenge of their in vivo analysis.